Aktualisasi Kinerja melalui Pelatihan Pembuatan Video Iklan Berbasis Artificial Intellegence untuk Mendukung Program Kerja Karang Taruna - Fitri Umardiyah; Misbaqhul Diky Kurniawan; Abdul Muslikh; Dian Kusuma Wardani; Bekti Widyaningsih (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
The work of the Youth Organization at Kudubanjar (Karang Taruna Kudubanjar) has not been implemented optimally in providing contributions and supplies to the community. This is caused by a lack of socialization and documentation of activities that have occurred, so that existing programs are sometimes not realized properly. To overcome this problem, this time the service will hold training aimed at increasing the effectiveness of the Youth Organization program. This training will cover several important aspects such as: effective socialization, activity documentation, project management, and use of technology. With this training, it is hoped that the Kudubanjar Youth Organization can be more effective in carrying out its programs and make a greater contribution to society. AI workshop for the young generation serves as the first step in preparing organizations to face rapid technological change, while opening up opportunities to create innovation and sustainable growth in the AI ​​era. As well as providing training in the form of using Artificial Intelligence (AI) in making public service advertisements, which function to encourage people to care about the environment, with an interesting delivery method, namely in the form of storytelling. Participants gain a strong knowledge base about AI and feel more confident in facing inevitable technological developments, and this activity will open the door to a brighter future full of potential for the younger generation, especially youth organization members.